PENGARUH METODE PERADILAN SEMU TERHADAP HASIL BELAJAR DEBAT SISWA KELAS X SMAN 5 SELAYAR - Rahman, Abdul; Sakaria, Sakaria (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
The Effect of the Moot Court Method on the Debate Learning Outcomes of Class X SMAN 5 Selayar. The purpose of this study was to examine the effect of moot court on student debate learning outcomes. This type of research is a type of quantitative research. The method in this study the author uses the experimental method. The population of this research is all students of Class X SMAN 5 Selayar which consists of 67 students and is divided into 4 classes. Sampling in this study using purposive sampling technique. The class that was chosen as the sample was class X IPA with 18 students. The data collection technique used in this research is a test technique which includes pre-test, treatment, and post-test. The data analysis technique in this research is quantitative data analysis in the form of statistical analysis. The result of this research is that the moot court method has a significant effect on the debate learning outcomes of the tenth graders of SMAN 5 Selayar.